Consortial purchasing, big deals, publisher concentration, open access and the scientific communication circuit - Anglada, Lluís (Anuario ThinkEPI, 2015)
Digital technology led to the emergence of a new economic model for scientific journals: consortial purchasing. This has been a breakthrough, providing library users widespread access to scientific information. In addition, the transition from individual paper subscriptions to electronic joint purchases has meant significant savings in processing costs for libraries. Nonetheless, consortium purchasing is not without problems: cost of journals continues to increase above the CPI, consortial agreements with publishers are inflexible, and pricing models become obsolete as time passes. In this state of impasse, open access appeared (and remains) on the scene, based on the powerful idea that information will be more useful the more easily it flows between its users. On the other hand, academic and research reputations have long been based on cumulated research citations: this is the "original sin" of the current scientific communication system, and until somebody figures out how to build an alternative system our high dependence on journals will persist.